1996 Olympic Games in Atlanta: The best male olleyball-teams: Italy - Zimmermann, B. (The Coach, 1997)
The homogenous team of Italy has since 1993 become the true champion in one World and two European championships, in the World Cup and the World League. The great potential of almost equally good players with differing individual abilities has enabled Italy to change play concepts and to influence partial play structures. In the matches against the Netherlands the team did not only perform very constantly but challenged the opponent with ever new tactical features. The aura of invincibility which had been created was broken for the first time when Italy lost the final in the World League 2:3 against the Dutch team. After the decisive loss in the Olympic final (the team against lost 2:3) many experts raised the question of the optimum composition of the team. Not least since the service was characterised by no advantageous ration between readiness to take a risk and efficacy for the play (30 minus in jumping spike serve). Totally Italy placed fourth of all teams in the service with Giani being the number 3 of all players. Since several years Italy has played with two main serve rece ption players to fight fluttering services (Bernardi, Papi, Bracci or Cantagalli). These players simultaneously have different strong points in their attacking play. In case of jumping spike services the middle blocker standing in the back row area (Giani, Gravina or Bovolenta) is incorporated into the serve reception formation. To fight very dangerous jumping spike services (by Van der Meulen NED or Fomin RUS) they form a four-players-serve-reception formation. In such cases the team also neglects back row attacks from position 1 by the diagonal player Giani (L4/L3/L2). With 53 % of perfect serve reception actions and 3 % misses the team shows mean values in this respect. The main receivers Papi (6) and Bernardi (9) with 60 to 70 % perform much better than the team at all in the reception of jumping spike services the subsidiary receivers still have reserves (30 and 40 % plus actions).